Psychological pedagogical bases and practical experience of creation of distance course - Naumenko S.A. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2010)
The modern problems of distance teaching are considered. The analysis of requirements and substantive provisions is carried out to creation of distance courses. Description of experience of their creation is resulted in distance departmental of Moodle teaching. The analysis of pedagogical and philosophical literature is conducted on the topic of research. Intercommunications of continuous education and distance teaching are rotined. The general is considered and different in terminology of distance teaching and education. The special attention is taken to psychological and pedagogical requirements of creation of distance course. The developed distance course was approved with the students of internal form of teaching from specialities: psychology, physical culture et al.